Desempenho ecofisiológico de uma espécie dioica (Myrsine coriácea) em diferentes fitofisionomias da Floresta Atlântica - Moreira, Vinicius Ferreira (2015)
Myrsine coriacea is a dioecious woody plant found in different phytophysiognomies in the biome of the Atlantic Forest, mainly in south and southeast regions of Brazil. It takes part in the feeding of many regional and / or migratory birds, and It shows potential for use in restoration projects of degraded areas. Therefore, the aim of this study is to evaluate the ecophysiological performance of female and male individuals m. cori in different vegetation types of the Atlantic Forest. It was evaluated characteristics morphological, physiological and biochemical responses, of male and female M. coriacea individuals situaded in three phytophysiognomies (Sandbank, Ombrophilous Forest and Altitude Fields). Female subjects showed an increase in ALT 34.8% higher than the male subjects. This result corresponds to the profile of dioecious plants, female plants which generally have higher growth rates, focusing on the production and maintenance of fruit. Environmental factors in altitude fields limit the photosynthetic responses without damaging the ecophysiological performance of M. coriacea, this behavior refers to the responses obtained in LA: SA which guaranteed the hydraulic efficiency and so the disposal and allocation of water and nutrients contributing to the production and development of the individuals. On the other hand, male plants obtained better performance in foliar resources, wich demonstrates that male individuals tend to allocate resources, mainly nitrogen, in the roots contributing to efficiency in the conduction and production of leaves and flowers in order to promote an effective pollination. Responses of FLA and CAR were pertinent in the performance of individuals as a result of environmental factors of each phytophysiognomy. Plants in altitude camps had a higher concentration of 41% compared to individuals of rain forest, and 11% from the Restinga. The altitude in Rain, made male and female subjects accumulate less metabolites in their leaves. In addition, FLA concentrations and CAR promoted defense conditions in M. coriacea, the effect of temperature variation. In conclusion M. coriacea indicated differences in the ecophysiological performance between the sexes, due to the trade - off found in dioecious plants, developing fundamental strategies to favor the survival of the specie resulting from the environmental characteristics of each field studied.